Psychological components of life quality in patients with discirculatory encephalopathy (stages I—II) treated with Tenoten - B. M. Doronin; I. A. Gribacheva; D. F. Moulyarov; V. B. Doronin (Бюллетень сибирской медицины, 2008)
Tenoten was used for the treatment of discirculatory encephalopathy (stages I—II). The article shows medical effects of the Tenoten using methods of statistic analysis.